2003
DOI: 10.1021/la0342666
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Behavior of Carbonate Species on Metal Oxide Surface:  Oxygen Scrambling between Adsorbed Carbon Dioxide and Oxide Surface

Abstract: The oxygen exchange between surface carbonate species and oxide surfaces was investigated by the temperature-programmed desorption (TPD) of C18O2 adsorbed on metal oxides, MgO, CaO, and ZrO2 at room temperature. Although desorption plots were quite different for these metal oxides, extensive oxygen exchange was commonly observed. The fraction of C16O2 in the total desorbed CO2 increased monotonically with desorption temperature, and each desorption peak in the plots for the total CO2 could not be characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 32 publications
2
36
0
Order By: Relevance
“…The amount of 3 that were formed before starting the reactions under scCO 2 condition were 0.33, 0.10, and 0.10 mmol for MgO, JRC-ALO-4, and mesoAl 2 O 3 , respectively. mesoAl 2 O 3 (#3) on the basis of the reports by Parkyns [41] as well as Tsuji and Hattori [42]. The CO 2 adsorbed on an active strong base site can migrate over the surface by the action of adjacent Lewis acid sites (Al 3+ ).…”
Section: Knoevenagel Reaction In Supercritical Comentioning
confidence: 96%
See 1 more Smart Citation
“…The amount of 3 that were formed before starting the reactions under scCO 2 condition were 0.33, 0.10, and 0.10 mmol for MgO, JRC-ALO-4, and mesoAl 2 O 3 , respectively. mesoAl 2 O 3 (#3) on the basis of the reports by Parkyns [41] as well as Tsuji and Hattori [42]. The CO 2 adsorbed on an active strong base site can migrate over the surface by the action of adjacent Lewis acid sites (Al 3+ ).…”
Section: Knoevenagel Reaction In Supercritical Comentioning
confidence: 96%
“…In addition, since the strength of the Lewis acid sites on alumina is strong, the surface migration of CO 2 would be ready to proceed. The Parkyns report demonstrated the existence of VII through infrared spectroscopy [41], while Tsuji and Hattori showed that the similar dynamic behavior of adsorbed CO 2 is seen even over CaO, of which Lewis acid sites (Ca 2+ ) are far weaker than those on alumina [42].…”
Section: Knoevenagel Reaction In Supercritical Comentioning
confidence: 98%
“…That can be rationalized as the result of low coordination of surface atoms and additional configurational degrees of freedom for phase formation. While there is evidence for surface migration of these carbonates on the oxide surfaces [Tsuji, 2003], [Liao, 2002], surface diffusion kinetics have not been extensively quantified. However, nearequilibrium CO 2 adsorption measurements can be used to estimate and compare CO 2 mobility on various oxide surfaces, as outlined below.…”
Section: Materials Selectionmentioning
confidence: 99%
“…At similar coverage, rare earth oxides have H ∆ of about 100-140 kJ/mol [Horiuchi, 1998a]; perovskites have lower H ∆ on the order of 50 kJ/mol [Kusakabe, 1994], [Martin, 1981], [Liu, 2005]. Notably, the interaction of CO 2 with basic sites on metal oxides, including perovskites, rare earth oxides and semiconducting oxides, is important in metal oxide-catalyzed reactions such as oxidative coupling of methane, CO 2 reforming of methane, and water gas shift [Tsuji, 2003], [Liu, 2005], [Istadi, 2004]. The catalytic activity of these oxides is consistent with positive but not overly strong surface affinity of CO 2 molecules, since strong CO 2 adsorption would result in poisoning of the active sites.…”
Section: Materials Selectionmentioning
confidence: 99%
“…It is highly probable that the surface MÀO bond breaking and the oxygen exchange processes take place through bidentate carbonate species formed at the Lewis acidbase (MÀO) pair sites. [5] Scarano et al have also found that the O±S exchange reaction occurs between a magnesium oxide surface and adsorbed CS 2 . [6] These results evoked the idea that a similar dynamic process with surface restructuring would be involved in the interactions with oxygen-containing organic molecules.…”
mentioning
confidence: 94%